An Overview of Kashmir Shaivism & Swami Lakshman Joo’s Contribution To It - Suhail Ahmad Thaker (Al Manhal Research Journal, 2025)
This article examines one of the very famous and ancient Hindu traditions, Kashmir Shaivism, its historical development, a brief introduction of ancient sages who shaped its academia, and more specifically, highlights the contributions of Lakshman Joo to this tradition, including his unique interpretations. His ability to draw the attention of foreign disciples in the 20th century, who not only learned this tradition and spent decades with Lakshman Joo but also devoted the rest of their lives to disseminate this tradition in the Western sphere. Additionally, the influence of ancient sages and Buddhist thought is also included in the paper, and it examines the significance of key figures such as Vasugupta and Abhinavagupta, whose writings and teachings have significantly shaped the foundational aspects of Kashmir Shaivism.